2005
DOI: 10.1523/jneurosci.4501-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II Modulates Rapid Eye Movement Sleep through Activation of Brainstem Cholinergic Neurons

Abstract: Urotensin II (UII) is a cyclic neuropeptide with strong vasoconstrictive activity in the peripheral vasculature. UII receptor mRNA is also expressed in the CNS, in particular in cholinergic neurons located in the mesopontine tegmental area, including the pedunculopontine tegmental (PPT) and lateral dorsal tegmental nuclei. This distribution suggests that the UII system is involved in functions regulated by acetylcholine, such as the sleep-wake cycle. Here, we tested the hypothesis that UII influences cholinerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 60 publications
2
39
0
1
Order By: Relevance
“…The presence of UT mRNA and UII binding sites in cholinergic neurons of the pedunculopontine tegmental nucleus (PPT) and the lateral dorsal tegmental area (Clark et al, 2001), two structures of the pons-midbrain transition area involved in the control of rapid eye movement (REM) sleep (Baghdoyan et al, 1984;Webster and Jones, 1988;Quattrochi et al, 1989;Steriade and McCarley, 1990), lends credence to the idea that the UII system may be implicated in the regulation of the sleep-wake cycle. Consistent with this hypothesis, intracerebroventricular administration of UII or local bilateral injection of UII into the PPT increases the number of REM sleep episodes in rat (Huitron-Resendiz et al, 2005;de Lecea and Bourgin, 2008). Interestingly, only a low dose (0.6 pmol) of UII significantly augments the amount of REM sleep, whereas a 10-fold higher dose is ineffective.…”
Section: A Effects Of Urotensin Ii/urotensin Ii-related Peptide In Tsupporting
confidence: 53%
See 2 more Smart Citations
“…The presence of UT mRNA and UII binding sites in cholinergic neurons of the pedunculopontine tegmental nucleus (PPT) and the lateral dorsal tegmental area (Clark et al, 2001), two structures of the pons-midbrain transition area involved in the control of rapid eye movement (REM) sleep (Baghdoyan et al, 1984;Webster and Jones, 1988;Quattrochi et al, 1989;Steriade and McCarley, 1990), lends credence to the idea that the UII system may be implicated in the regulation of the sleep-wake cycle. Consistent with this hypothesis, intracerebroventricular administration of UII or local bilateral injection of UII into the PPT increases the number of REM sleep episodes in rat (Huitron-Resendiz et al, 2005;de Lecea and Bourgin, 2008). Interestingly, only a low dose (0.6 pmol) of UII significantly augments the amount of REM sleep, whereas a 10-fold higher dose is ineffective.…”
Section: A Effects Of Urotensin Ii/urotensin Ii-related Peptide In Tsupporting
confidence: 53%
“…The UT antagonist SB-710411 blocks the UII-induced REM sleep response. Whole cell recording from rat brain slices revealed that UII triggers cholinergic PPT neurons by activating a slow inward current (Huitron-Resendiz et al, 2005).…”
Section: A Effects Of Urotensin Ii/urotensin Ii-related Peptide In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, UII is becoming increasingly implicated in a variety of mood and sleep processes. UII plays a role in releasing norepinephrine in the cerebral cortex (62), influences rapid eye movement in the rat via direct cholinergic activation (53), and alters behavior in mice upon central administration (30). UII is also implicated in digestive behavior.…”
mentioning
confidence: 99%
“…For instance, expression of the gene for 5-hydroxytryptamine 2c (5-HT 2c ) receptors is enhanced in the PRE-HMN but not in the HMN (Table 1), yet we do not know what effect the selective agonism of these receptors would have on hypoglossal motor output, or if 5-HT 2c receptor-positive neurons innervate the HMN. Similarly, the effect of modulating the activity of Urotensin II receptors on hypoglossal motor output has not been determined but would be worth investigating given that Urotensin II receptor RNA shows a high degree of differential expression at the HMN (being 12.6 fold higher than for the rest of the brain), and that Urotensin II receptor activation has potent excitatory effects on central cholinergic neurons 6365 .…”
Section: Mapping Potential Drug Targets In the Circuitry Controllimentioning
confidence: 99%